La naturaleza de los derechos : el debate Dworkin-Posner (2017)
One of the most relevant issues for contemporary theories of adjudication is that of the nature of rights. The debate between Richard Posner and Ronald Dworkin is largely concerned with the question of whether there is a distinction between rights and collective goals. This essay examines the implications of said distinction for judicial decision making. Firstly, not acknowledging it implies that rights are taken to be means that may be sacrificed in order to achieve a common aim. Secondly, not acknowledging this distinction implies denying that rights are derived from some dimension of morality, therefore challenging the claim that hard cases may be decided objectively and that there are right answers to legal questions.--Tomado del Formato de Documento de Grado.